Governance and Corruption: Evaluating Anti-Corruption Policies and Their Effectiveness in Strengthening Institutional Integrity - Maolani, Dedeng Yusuf (GoAcademica Research & Publishing, 2024)
This study investigates the effectiveness of anti-corruption policies in enhancing institutional integrity and governance across various contexts. By conducting a comprehensive literature review and comparative analysis of selected case studies, this research aims to provide a nuanced understanding of the mechanisms and factors that contribute to successful anti-corruption measures. The literature review explores definitions, types, and theoretical frameworks of corruption, as well as an overview of existing anti-corruption policies. The methodology includes qualitative data collection through document analysis and interviews, with case studies selected based on criteria such as geographical diversity and varying governance structures. The analysis highlights the effectiveness of different anti-corruption strategies, considering contextual factors such as political will, institutional capacity, and socio-economic conditions. Findings reveal that robust governance structures, transparency, and community involvement are critical for the success of anti-corruption initiatives. The study also identifies common challenges, including resistance to change, inadequate enforcement mechanisms, and the complexity of corruption networks. Based on these insights, the research provides policy recommendations for designing and implementing effective anti-corruption measures, emphasizing the importance of tailored approaches that consider local contexts. This study contributes to the broader discourse on governance and corruption, offering practical guidance for policymakers and practitioners aiming to strengthen institutional integrity and reduce corruption.